PROPER NUTRITION - Kakhorova Karomatkhon Sovronbayevna; Xatamboyeva Xurshidabonu Axmadjon qizi (Western European Studies, 2025)
This article explores the critical role of proper nutrition in promoting health, preventing disease, and enhancing quality of life. It reviews current scientific literature, outlines methods for assessing nutritional needs, presents key findings on the impact of balanced diets, and discusses implications for individuals and public health. The article concludes with practical suggestions for adopting healthier eating habits.
Keywords: Nutrition; balanced diet